Prolonged Vancomycin‐Induced Linear IgA Disease in a Patient With Renal Failure - Kaori Takezawa; Reiko Noborio; Yuki Nomura; Takahiro Kiyohara; Mako Mine; Takashi Hashimoto (JEADV Clinical Practice)
ABSTRACT A 64‐year‐old man with pneumococcal septic shock and subsequent renal failure underwent treatments with antibiotics including intravenous vancomycin (VCM). Blistering skin lesions appeared 10 days after the initiation of VCM. When the patient was transferred to us 5 months later, blisters with erythema were still observed on the abdomen and thighs. Histopathological examination revealed subepidermal blister with infiltration of eosinophils and neutrophils, and direct immunofluorescence revealed linear IgA deposition at the basement membrane zone. The diagnosis of linear IgA disease (LAD)was made, and drug‐induced LAD by VCM was suspected, because of the episode of the blister development 10 days after the first VCM administration. Although the results of various sero‐immunological tests were negative, IgA reactivity with type Ⅶ collagen was detected by VCM‐treated ELISA, which further suggested the diagnosis of VCM‐induced LAD. The possible mechanism for the prolonged disease course was speculated.